Kombinasi Discovery Learning dengan Multimedia Interaktif dalam Meningkatkan Daya Kritis Siswa - Yani, Ni Luh Sinta; Santoso, Jarot Tri Bowo (Jurnal Pendidikan Ekonomi Undiksha, 2024)
The purpose of this study was to analyze the application of the interactive multimedia-assisted discovery learning model to improve students' critical thinking skills in economics subjects at SMA Negeri 1 Busungbiu. This research is classroom action research that aims to find out how the Discovery model is applied. Learning to improve critical thinking skills on demand and supply subject matter. This research took place in two cycles, consisting of four stages, namely: planning, action/implementation, observation, and evaluation. Data collection was carried out using a critical thinking ability test. Students' critical thinking skills increased after applying the discovery learning model. The average critical thinking ability of students is 55.16 in the moderately critical category. Meanwhile, students' critical thinking skills increased to 79.74 in the critical category.